Penerapan Akuntansi Pertanggungjawaban Sebagai Alat Bantu Manajemen Dalam Menilai Kinerja Bagian Produksi (Studi Kasus Pada PT. Cahaya Buana Intitama) - Hasibuan, David HM; Sari, Sartika Setia (Jurnal Ilmiah Akuntansi Kesatuan, 2016)
Responsibility accounting is an accounting system that is based on an organizational structure that clearly separates the duties, power, and responsibilities of each level of management. By establishing responsibility centers for accumulating and reporting cost center, as well as the accountability reporting centers to be assessed performance. The purpose of this study is to conduct an evaluation of the work of responsibility centers to improve the company's operations in the near future, based on the accountability of each part is related to the company in the form of performance assessment activities of the company in order to determine the deviations that occur in each responsibility center as well as an analysis of the implementation of responsibility accounting as a management tool in assessing the performance of the production line. Application of responsibility accounting in PT. Cahaya Buana Intitama is already well underway. This can be seen from the quality of target budget and plan production based on the consumers’ satisfaction. Performance parts production also has shown good performance results. It is all in accordance with the job description, following the ISO that has been determined by the company. The research concludes that the responsibility accounting plays important role in inside appraisal the performance from center-center of accountability. Therefor proves that the responsibility accounting applied by PT. Cahaya Buana Intitama is beneficial for the assessment of performance against part the production. Thus, the company will not be experiencing difficulties in determining which parts may issue costs in which eventually will be influential on decision-making as well as overall improvement on the company’s performance.